The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Redéfinir l’endométriose : De la critique féministe à la santé environnementale - Čapek, Stella M. (Sur la piste environnementale : Menaces sanitaires et mobilisations profanes, 2013)
Code: Sur la piste environnementale : Menaces sanitaires et mobilisations profanes
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; inégalités; justice reproductive; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; écoféminisme; états-unis